Guide for the preparation of flowcharts on institutional processes - Organizational Design Division (Inter-American Institute for Cooperation on Agriculture, 2022)
The guide is a tool to assist in the designing of flowcharts, as a means of strengthening the Institute’s process culture, to enhance institutional efficiency and productivity. It provides users with the requisite guidance on how to prepare a standardized graphical representation on the execution and optimization of processes. It includes instructions on how to compile information on activities in each process, undertake an analysis to pinpoint areas for improvement and map the actions performed in each process to obtain the desired results.